Understanding Lymphatic Drainage Pathways of the Ovaries to Predict Sites for Sentinel Nodes in Ovarian Cancer. Issue 8 (October 2015) - Kleppe, Marjolein; Kraima, Anne C.; Kruitwagen, Roy F.P.M.; Van Gorp, Toon; Smit, Noeska N.; van Munsteren, Jacoba C.; DeRuiter, Marco C.
Abstract : Objective: In ovarian cancer, detection of sentinel nodes is an upcoming procedure. Perioperative determination of the patient's sentinel node(s) might prevent a radical lymphadenectomy and associated morbidity. It is essential to understand the lymphatic drainage pathways of the ovaries, which are surprisingly up till now poorly investigated, to predict the anatomical regions where sentinel nodes can be found. We aimed to describe the lymphatic drainage pathways of the human ovaries including their compartmental fascia borders. Methods: A series of 3 human female fetuses and tissues samples from 1 human cadaveric specimen were studied. Immunohistochemical analysis was performed on paraffin-embedded transverse sections (8 or 10 μm) using antibodies against Lyve-1, S100, and α-smooth muscle actin to identify the lymphatic endothelium, Schwann, and smooth muscle cells, respectively. Three-dimensional reconstructions were created. Results: Two major and 1 minor lymphatic drainage pathways from the ovaries were detected. One pathway drained via the proper ligament of the ovaries (ovarian ligament) toward the lymph nodes in the obturator fossa and the internal iliac artery. Another pathway drained the ovaries via the suspensory ligament (infundibulopelvic ligament) toward the para-aortic and paracaval lymph nodes. A third minor pathway drained the ovaries via the round ligament to the inguinal lymph nodes. Lymph vessels draining the fallopian tube all followed the lymphatic drainage pathways of the ovaries. Conclusions: The lymphatic drainage pathways of the ovaries invariably run via the suspensory ligament (infundibulopelvic ligament) and the proper ligament of the ovaries (ovarian ligament), as well as through the round ligament of the uterus. Because ovarian cancer might spread lymphogenously via these routes, the sentinel node can be detected in the para-aortic and paracaval regions, obturator fossa and surrounding internal iliac arteries, and inguinal regions. These findings support the strategy of injecting tracers in both ovarian ligaments to identify sentinel nodes. Abstract : Supplemental digital content is available in the text.